Ruminants reveal Eocene Asiatic palaeobiogeographical provinces as the origin of diachronous mammalian Oligocene dispersals into Europe - Bastien Mennecart (Nature Portfolio, 2021)
Abstract Faunal provincialism between the North and South parts of Eastern Asia is shown to have been in place since the late Eocene. This provincialism structured the mammalian dispersals across Eurasia for millions of years and provides insights into both palaeonvironments and palaeoclimate zonation. In addition, this study reveals the oldest record of a crown ruminant (Iberomeryx from Shinao, China). Ecologically, as well as economically, ruminant artiodactyls are one of the most important large mammal groups today. The revision of the ruminants from the Shinao Formation, from the Caijiachong marls and Xiaerhete, resulted in two new taxa and shows that the different provinces were populated by distinct taxa living in different environments, dominated by the monsoon in the South and drier conditions in the North. Evaluating this result in a Eurasian context demonstrates that the dispersals from Asia to Europe was complex. These results confirm that there were at least two dispersal events, distinct in space and time: the Grande-Coupure from Northern and Central Asia along the North ca. 34 Mya and the Bachitherium dispersal event from the Southern province along a southerly route ca. 31 Mya.